Uji Irigasi Tetes Bertingkat Empat Pada Media Tanaman Campuran Tanah Cocopeat dan Kompos Ternak Terhadap Resapan dan Lengas Tanah - Negara, I Dewa Gede Jaya; Supriyadi, Anid; Pracoyo, Atas; Yasa, I Wayan; Saleh, Ramdan (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
The utilization of multilevel drip irrigation needs to be supported by adequate planting media so that the provision of irrigation water is optimal. The planting media used practically uses soil mixed with livestock waste compost and cocopeat in polybags. This test aims to determine the ability of drip irrigation water absorption by the planting media in the form of irrigation depth and soil moisture provision and prediction of irrigation application with a certain duration. The study was conducted on a Â½â€ PVC pipe drip irrigation network with a 2 lt/hour emitter, on a land size of 2 m x 4m x 2m with a water source from PDAM water which is stored in a tank with a capacity of 150 liters and a height of 2.5 m. The test data taken includes data on the distribution of irrigation volume, irrigation depth and soil moisture. The results of the analysis showed that the distribution of drip irrigation depth in cocopeat media ranged from 7.5 cm - 12 cm in 5 minutes, while in rice husks the absorption was around 6.5 cm - 10 cm for the planting media level, with an average Cu of 96% which is very good. The maximum soil moisture that can be provided by four-tiered drip irrigation at a duration of 5 minutes is 30.5% in the early growth phase and at a duration of 10 minutes the average soil moisture is 15%, in the Vegetative phase of plant growth until fruit ripening. So the high irrigation infiltration rate in cocopeat media has the potential to be applied to plants that have long or deep roots, while planting media with rice husks has the potential to be applied to plants with short roots such as vegetables.